Pengaruh Metode Outdoor Learning Terhadap Kemampuan Menulis Karangan Deskripsi Siswa Kelas IV SDI Sorobaya Kabupaten Gowa - Andi Rizki Dani; Andi Sukri Syamsuri; Muhammad Saeful (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
The main problem in this research is whether the outdoor learning method has an influence on the ability to write descriptive essays for class IV SDI Sorobaya students. This research aims to determine the effect of applying outdoor learning methods on the ability to write descriptive essays for class IV SDI Sorobaya students. The type of research used is an experiment in the form of an experiment using a one group pretest-posttest design. The sample in this research was 11 class IV SDI Sorobaya students. Data collection was carried out using the results of the descriptive essay writing assessment. The data obtained was then explained using statistical analysis techniques, namely descriptive statistics and inferential statistics. After analyzing the data, the author found that student learning outcomes before using outdoor learning methods were classified as low, namely the average score of the pre-test results was 41.27. The average value of the post test results is 67.27. After obtaining Tcount 4.579 and Ttable 2.228, we get tCount > tTable or 4.579 > 2.228. Based on the results of the calculated t and t table, it can be concluded that the use of outdoor learning methods influences the ability to write descriptive essays for class IV SDI Sorobaya students.